Characterizing ambient concentration of PM10 in urban environment of central south China. Issue 3 (May 2015) - Deng, Qihong; Lu, Chan; Yu, Chuck
China has been experiencing high particulate air pollution in spite of a decline in concentration over the past decade, but the key factors affecting the variation are not clear. This study characterizes the ambient concentration of PM10 in urban environment of Changsha. Hourly PM10 concentrations and meteorological parameters were monitored over a year in 2008 at the city centre of Changsha in central south China. The variation in ambient PM10 concentration and its association with meteorological parameters were statistically analyzed. The concentration could vary in seasons and week days; higher particulate concentration was found in cold seasons and weekdays than in warm seasons and weekends. The diurnal variations showed a bimodal distribution in the morning and evening rush hours. The temporal variation in PM10 concentration was shown to be dominated by both anthropogenic sources and meteorological conditions. The daytime peak is mainly due to human activities but high concentration during night-time is attributable to the unfavourable meteorological conditions, not sufficient for dispersion or disposition of pollutants. High concentration during night-time was responsible for the occurrence of exceedance episodes. Our work indicates that controlling PM10 concentration during night-time is an effective way to reduce episodes in China. The characterization of air pollution in an urban city of central south China would provide data to inform control strategies and distribution of pollution in the country.